Block copolymer pellets, adhesive composition, and stretch film

By using characteristic petroleum-based powder in the block copolyester particles and setting appropriate physical properties, the problem of easy block copolyester particles being blocked during molding and processing is solved, and the effects of high blocking resistance, transparency and adhesion are achieved.

JP7670049B2Active Publication Date: 2025-04-30ZEON CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022503294
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-25
Filing Date
2021-02-17
Publication Date
2025-04-30
Estimated Expiration
2041-02-17

AI Technical Summary

Technical Problem

Existing block copolyester particles are prone to blockage during molding and processing, and use of blocking agents can lead to a decrease in opacity and transparency.

Method used

Petroleum-based powders containing specific surface area, particle size, volume density and melting point are used as powder agents, and specific Shore A hardness and BET special surface areas are set in the block copolyester particles to inhibit the occurrence of powderization while maintaining blocking resistance and transparency.

Benefits of technology

Block copolyester particles with high block resistance, transparency and adhesion are realized, and can effectively prevent powderization and improve the performance of the finished product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670049000001
    Figure 0007670049000001
  • Figure 0007670049000002
    Figure 0007670049000002
  • Figure 0007670049000003
    Figure 0007670049000003
Patent Text Reader

Abstract

Provided are block-copolymer pellets comprising 100 parts by weight of pellets of a block copolymer (A) and 0.01-5 parts by weight of a hydrocarbon-based dusting powder (B), wherein the block copolymer (A) comprises at least one aromatic-vinyl polymer block and at least one conjugated-diene polymer block and the hydrocarbon-based dusting powder (B) has a BET specific surface area of 0.50-3.00 m2 / g, a volume-average particle diameter of 2.0-20 μm, a bulk density of 0.10-0.34 g / cm3, and a melting point of 75°C or greater. The block-copolymer pellets have a Shore A hardness of 10-80 and a BET specific surface area, as determined by Kr adsorption method, of 0.001-0.05 m2 / g.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to block copolymer pellets which are suppressed in generating dust, have excellent blocking resistance and transparency, and exhibit high adhesion to adherends, and to a pressure-sensitive adhesive composition and a stretch film obtained by using such block copolymer pellets. [Background technology]

[0002] Block copolymers having an aromatic vinyl polymer block and a conjugated diene polymer block, such as styrene-isoprene-styrene block copolymer (SIS) and styrene-butadiene-styrene block copolymer (SBS), are thermoplastic elastomers having characteristic properties in various respects and are therefore used in a variety of applications (see, for example, Patent Document 1).

[0003] On the other hand, such a block copolymer having an aromatic vinyl polymer block and a conjugated diene polymer block has a problem that it is viscous and prone to blocking, and therefore, when such a block copolymer is molded into pellets for processing, it is difficult to handle.

[0004] In order to prevent blocking of pellets made of a block copolymer having an aromatic vinyl polymer block and a conjugated diene polymer block, a method is usually adopted in which an antiblocking agent made of fine powder such as talc or fatty acid amide is attached to the pellet surface to prevent the pellets from directly contacting each other. However, the use of such an antiblocking agent causes problems such as turbidity and loss of transparency. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-69565 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in view of the above circumstances, and aims to provide a block copolymer pellet that suppresses dusting, has excellent blocking resistance and transparency, and exhibits high adhesion to an adherend. Another aim of the present invention is to provide a pressure-sensitive adhesive composition and a stretch film obtained by using such a block copolymer pellet. [Means for solving the problem]

[0007] The present inventors have conducted studies to achieve the above-mentioned object, and have found that in a block copolymer pellet comprising a pelletized product of a block copolymer including a block copolymer having an aromatic vinyl polymer block and a conjugated diene polymer block, and a dusting agent, the above-mentioned object can be achieved by using a specific amount of a hydrocarbon dusting agent having a specific range of specific surface area, volume average particle size, bulk density, and melting point as the dusting agent, and by setting the Shore A hardness and BET specific surface area of ​​the block copolymer pellets within specific ranges, thereby completing the present invention.

[0008] That is, according to the present invention, there is provided a block copolymer pellet comprising 100 parts by weight of a pellet-formed body of a block copolymer (A) and 0.01 to 5 parts by weight of a hydrocarbon-based dusting agent (B), The block copolymer (A) has at least one aromatic vinyl polymer block and at least one conjugated diene polymer block, The hydrocarbon dusting agent (B) has a BET specific surface area of ​​0.50 to 3.00 m 2 / g, volume average particle size is 2.0 to 20 μm, bulk density is 0.10 to 0.34 g / cm 3 , the melting point is 75°C or more; The block copolymer pellets have a Shore A hardness of 10 to 80 and a BET specific surface area of ​​0.001 to 0.05 m as measured by a Kr adsorption method.2 / g of block copolymer pellets are provided.

[0009] In the present invention, the hydrocarbon dusting agent (B) preferably contains particles having a particle size of 20 μm or more in a proportion of 3 to 40% by volume. In the present invention, it is preferable that the pellet molded product further contains 0.5 to 5.0 parts by weight of a polystyrene polymer based on 100 parts by weight of the block copolymer (A). In the present invention, the hydrocarbon dusting agent (B) is preferably a dusting agent made of a polyolefin polymer. In the present invention, the content of aromatic vinyl monomer units in the block copolymer (A) is preferably 10 to 50% by weight. In the present invention, it is preferred that the aromatic vinyl polymer block is a polymer block containing styrene units as main repeating units, and the conjugated diene polymer block is a polymer block containing isoprene units as main repeating units.

[0010] According to the present invention, there is also provided a pressure-sensitive adhesive composition obtained by using the above block copolymer pellets. Furthermore, according to the present invention, there is provided a stretch film obtained by using the above block copolymer pellets. Effect of the Invention

[0011] According to the present invention, it is possible to provide a block copolymer pellet which is suppressed in generation of dust, has excellent blocking resistance and transparency, and exhibits high adhesion to an adherend. In addition, according to the present invention, it is also possible to provide a pressure-sensitive adhesive composition and a stretch film obtained by using such a block copolymer pellet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The block copolymer pellets of the present invention are A block copolymer pellet comprising 100 parts by weight of a pellet-formed body of a block copolymer (A) and 0.01 to 5 parts by weight of a hydrocarbon-based dusting agent (B), The block copolymer (A) has at least one aromatic vinyl polymer block and at least one conjugated diene polymer block, The hydrocarbon dusting agent (B) has a BET specific surface area of ​​0.50 to 3.00 m 2 / g, volume average particle size is 2.0 to 20 μm, bulk density is 0.10 to 0.34 g / cm 3 , the melting point is 75°C or more; The block copolymer pellets of the present invention have a Shore A hardness of 10 to 80 and a BET specific surface area of ​​0.001 to 0.05 m as measured by the Kr adsorption method. 2 / g.

[0013] <Block copolymer (A)> The block copolymer (A) used in the present invention has at least one aromatic vinyl polymer block and at least one conjugated diene polymer block.

[0014] The aromatic vinyl polymer block is a polymer block constituted by aromatic vinyl monomer units obtained by polymerizing an aromatic vinyl monomer as a main repeating unit.

[0015] The content of aromatic vinyl monomer units in the aromatic vinyl polymer block is preferably 80% by weight or more, more preferably 90% by weight or more, and particularly preferably substantially 100% by weight.

[0016] The aromatic vinyl monomer used to form the aromatic vinyl polymer block is not particularly limited as long as it is an aromatic vinyl compound. For example, styrene; styrenes having an alkyl group as a substituent, such as α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2,4-diisopropylstyrene, 2,4-dimethylstyrene, 4-t-butylstyrene, and 5-t-butyl-2-methylstyrene; styrenes having a halogen atom as a substituent, such as 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, 4-bromostyrene, and 2,4-dibromostyrene; styrenes having an alkyl group and a halogen atom as a substituent, such as 2-methyl-4,6-dichlorostyrene; vinylnaphthalene; and the like. These aromatic vinyl monomers can be used alone or in combination of two or more. Among these, from the viewpoint of easy availability, styrene and styrenes having an alkyl group as a substituent are preferred, and styrene is particularly preferred.

[0017] The aromatic vinyl polymer block may contain other monomer units as long as the aromatic vinyl monomer unit is the main repeating unit. Examples of monomers constituting monomer units other than aromatic vinyl monomer units that can be contained in the aromatic vinyl polymer block include conjugated diene monomers such as 1,3-butadiene and isoprene (2-methyl-1,3-butadiene); α,β-unsaturated nitrile monomers such as acrylonitrile and methacrylonitrile; unsaturated carboxylic acid monomers such as acrylic acid, methacrylic acid, maleic acid, fumaric acid, and itaconic acid; unsaturated carboxylic acid anhydrides such as maleic anhydride, butenyl succinic anhydride, tetrahydrophthalic anhydride, and citraconic anhydride; unsaturated carboxylic acid ester monomers such as methyl acrylate, ethyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, and 2-ethylhexyl methacrylate; and non-conjugated diene monomers preferably having 5 to 12 carbon atoms, such as 1,4-pentadiene and 1,4-hexadiene.

[0018] In addition, when the block copolymer (A) has a plurality of aromatic vinyl polymer blocks, the plurality of aromatic vinyl polymer blocks may be the same or different from each other.

[0019] The content of aromatic vinyl monomer units relative to the total monomer units constituting the block copolymer (A) is not particularly limited, but is preferably 10 to 50% by weight, more preferably 11 to 40% by weight, and even more preferably 12 to 38% by weight. When the content of aromatic vinyl monomer units in the block copolymer (A) is within such a range, the block copolymer can have excellent adhesive properties and moldability. The content of aromatic vinyl monomer units in the block copolymer (A) is 1 It can be measured by H-NMR. Alternatively, when all the polymer components constituting the block copolymer (A) are composed of only aromatic vinyl monomer units and conjugated diene monomer units, the polymer components in the block copolymer (A) are decomposed by ozonolysis according to the method described in Rubber Chem.Technol., 45, 1295 (1972), and then reduced by lithium aluminum hydride, whereby the conjugated diene monomer unit portion is decomposed and only the aromatic vinyl monomer unit portion can be extracted, so that the total aromatic vinyl monomer unit content can be easily measured.

[0020] The conjugated diene polymer block is a polymer block constituted of a conjugated diene monomer unit obtained by polymerizing a conjugated diene monomer as a main repeating unit.

[0021] The content of the conjugated diene monomer unit in the conjugated diene polymer block is preferably 80% by weight or more, more preferably 90% by weight or more, and particularly preferably substantially 100% by weight.

[0022] The conjugated diene monomer used to form the conjugated diene polymer block is not particularly limited as long as it is a conjugated diene compound. For example, 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, etc. can be exemplified. These conjugated diene monomers can be used alone or in combination of two or more. Among these, it is preferable to use 1,3-butadiene and / or isoprene, and it is particularly preferable to use isoprene. By forming the conjugated diene polymer block from isoprene units, it is possible to obtain excellent adhesion properties and flexibility.

[0023] The conjugated diene polymer block may contain other monomer units as long as the conjugated diene monomer unit is the main repeating unit. Examples of monomers constituting monomer units other than the conjugated diene monomer unit that can be contained in the conjugated diene polymer block include aromatic vinyl monomers such as styrene and α-methylstyrene, α,β-unsaturated nitrile monomers, unsaturated carboxylic acid monomers, unsaturated carboxylic anhydrides, unsaturated carboxylic ester monomers, and non-conjugated diene monomers. The α,β-unsaturated nitrile monomers, unsaturated carboxylic acid monomers, unsaturated carboxylic anhydrides, unsaturated carboxylic ester monomers, and non-conjugated diene monomers can be the same as the monomers constituting monomer units other than the aromatic vinyl monomer unit that can be contained in the aromatic vinyl polymer block.

[0024] In addition, when the block copolymer (A) has a plurality of conjugated diene polymer blocks, the plurality of conjugated diene polymer blocks may be the same or different from each other. Furthermore, a part of the unsaturated bonds of the conjugated diene polymer blocks may be hydrogenated.

[0025] The vinyl bond content of the conjugated diene polymer block (the ratio of 1,2-vinyl bonds and 3,4-vinyl bonds to all conjugated diene monomer units in the conjugated diene polymer block) is not particularly limited, but is preferably 1 to 20 mol %, more preferably 2 to 15 mol %, and particularly preferably 3 to 10 mol %. The vinyl bond content of the conjugated diene polymer block is 1 It can be measured using H-NMR.

[0026] The block copolymer (A) may have at least one aromatic vinyl polymer block and at least one conjugated diene polymer block, and may contain a plurality of copolymer components differing in the number of polymer blocks or in the bonding form thereof.

[0027] Specific examples of the form of the block copolymer (A) include an aromatic vinyl-conjugated diene diblock copolymer component represented as Ar-D, Ar-D-Ar, or (Ar-D) where Ar represents an aromatic vinyl polymer block, D represents a conjugated diene polymer block, X represents a single bond or a residue of a coupling agent, and n represents an integer of 2 or more. n -A vinyl aromatic-conjugated diene-vinyl aromatic block copolymer component represented as X, D-Ar-D or (D-Ar) n Examples of the block copolymer component include, but are not limited to, a conjugated diene-aromatic vinyl-conjugated diene block copolymer component represented as Ar-X, an aromatic vinyl-conjugated diene-aromatic vinyl-conjugated diene block copolymer component represented as Ar-D-Ar-D, and a mixture of block copolymer components obtained by mixing two or more of these in any combination.

[0028] Among these, the block copolymer (A) is an aromatic vinyl-conjugated diene diblock copolymer component represented by Ar-D and Ar-D-Ar or (Ar-D) n Mixtures with the vinyl aromatic-conjugated diene-vinyl aromatic block copolymer component represented as -X are preferred.

[0029] The aromatic vinyl-conjugated diene diblock copolymer component represented by Ar-D is a diblock copolymer component having one aromatic vinyl polymer block and one conjugated diene polymer block. The content of the diblock copolymer component in the block copolymer (A) is not particularly limited, but is preferably 0 to 90% by weight, more preferably 0 to 80% by weight, and further preferably 10 to 70% by weight.

[0030] The aromatic vinyl-conjugated diene-aromatic vinyl block copolymer component represented by Ar-D-Ar is a block copolymer component having two aromatic vinyl polymer blocks. In this block copolymer component, the weight average molecular weights of the two aromatic vinyl polymer blocks may be the same or different. That is, the block copolymer component represented by Ar-D-Ar may be a symmetric aromatic vinyl-conjugated diene-aromatic vinyl block copolymer component in which an aromatic vinyl polymer block having a predetermined weight average molecular weight, a conjugated diene polymer block, and an aromatic vinyl polymer block having a predetermined weight average molecular weight are connected in this order, or may be an asymmetric aromatic vinyl-conjugated diene-aromatic vinyl block copolymer component in which an aromatic vinyl polymer block having a relatively small weight average molecular weight, a conjugated diene polymer block, and an aromatic vinyl polymer block having a relatively large weight average molecular weight are connected in this order.

[0031] Also, (Ar-D) nThe aromatic vinyl-conjugated diene-aromatic vinyl block copolymer component represented by -X is a block copolymer component constituted by two or more diblock bodies formed by bonding an aromatic vinyl polymer block and a conjugated diene polymer block, which are bonded directly by a single bond or via a residue of a coupling agent. The coupling agent constituting the residue of the coupling agent will be described later. The number of diblock bodies (Ar-D) bonded (i.e., n) is not particularly limited as long as it is 2 or more, and block copolymer components in which diblock bodies are bonded in different numbers may be mixed. n is not particularly limited as long as it is an integer of 2 or more, but is usually an integer of 2 to 8, preferably an integer of 2 to 4.

[0032] The weight average molecular weight of the block copolymer (A) is not particularly limited, but is preferably from 30,000 to 500,000, more preferably from 35,000 to 400,000, and even more preferably from 40,000 to 250,000.

[0033] The weight average molecular weight of each polymer block of the block copolymer (A) is not particularly limited, and the weight average molecular weight of the aromatic vinyl polymer block is preferably 6,000 to 400,000, more preferably 6,000 to 370,000. If the weight average molecular weight of the aromatic vinyl polymer block is too small, the adhesive properties may be poor, and if the weight average molecular weight of the aromatic vinyl polymer block is too large, the viscosity may be high, and production of the block copolymer (A) may be difficult.

[0034] Furthermore, the weight average molecular weight of the conjugated diene polymer block is preferably 18,000 to 400,000, and more preferably 19,000 to 350,000. If the weight average molecular weight of the conjugated diene polymer block is too small, the adhesive properties may be poor, whereas if the weight average molecular weight of the conjugated diene polymer block is too large, the viscosity may be high.

[0035] The molecular weight distribution, which is expressed by the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of each polymer block constituting the block copolymer (A), is not particularly limited, but is preferably 1.1 or less, more preferably 1.05 or less.

[0036] The weight average molecular weight and number average molecular weight of the block copolymer (A), each copolymer component, and each polymer block are determined based on the value converted into polystyrene by high performance liquid chromatography. More specifically, the weight average molecular weight and number average molecular weight can be determined as the polystyrene converted molecular weight by high performance liquid chromatography using tetrahydrofuran as a carrier at a flow rate of 0.35 ml / min. The apparatus used is a Tosoh HLC8320, the column is a combination of three Showa Denko Shodex KF-404HQ columns (column temperature 40°C), and the detectors are a differential refractometer and an ultraviolet detector. The molecular weight can be calibrated at 12 points of standard polystyrene (5 to 3 million) manufactured by Polymer Laboratory.

[0037] The block copolymer (A) used in the present invention may contain components other than the block copolymer components, as necessary, such as antioxidants, softeners, tackifiers, antibacterial agents, light stabilizers, UV absorbers, dyes, lubricants, crosslinking agents, and crosslinking accelerators.

[0038] The method for producing the block copolymer (A) used in the present invention is not particularly limited, and for example, it can be produced according to a conventional method for producing a block copolymer. For example, when the block copolymer (A) contains an aromatic vinyl-conjugated diene diblock copolymer component (A1) represented by Ar-D and an aromatic vinyl-conjugated diene-aromatic vinyl triblock copolymer component (A2) represented by (Ar-D)2-X, it can be produced by the following method.

[0039] That is, the block copolymer (A) can be produced by a production method including the following steps (1) to (4). (1): A process for obtaining a solution containing an aromatic vinyl polymer having an active terminal by polymerizing an aromatic vinyl monomer in a solvent using a polymerization initiator. (2): A step of adding a conjugated diene monomer to the solution containing the aromatic vinyl polymer having active terminals obtained in the above step (1) and polymerizing the conjugated diene monomer to obtain a solution containing an aromatic vinyl-conjugated diene block copolymer having active terminals. (3): A step of adding a bifunctional coupling agent to the solution containing the aromatic vinyl-conjugated diene block copolymer having active terminals obtained in the above step (2) in an amount such that the total amount of functional groups relative to the active terminals is less than 1 molar equivalent, thereby coupling a part of the aromatic vinyl-conjugated diene block copolymer having active terminals to obtain a solution containing a diblock copolymer component (A1) and a triblock copolymer component (A2). (4): A step of recovering a block copolymer (A) containing a diblock copolymer component (A1) and a triblock copolymer component (A2) from the solution containing the diblock copolymer component (A1) and the block copolymer component (A2) obtained in the above step (3).

[0040] <Process (1)> In the above production method, first, in step (1), an aromatic vinyl monomer is polymerized in a solvent using a polymerization initiator to obtain a solution containing an aromatic vinyl polymer having an active end.

[0041] As the polymerization initiator, a polymerization initiator known to have an anionic polymerization activity for an aromatic vinyl monomer and a conjugated diene monomer can be used. Examples of the polymerization initiator include an organic alkali metal compound, an organic alkaline earth metal compound, and an organic lanthanoid series rare earth metal compound.

[0042] As the organic alkali metal compound, an organic lithium compound having one or more lithium atoms in the molecule is particularly preferably used.Specific examples of the organic alkali metal compound include organic monolithium compounds such as ethyl lithium, n-propyl lithium, isopropyl lithium, n-butyl lithium, sec-butyl lithium, t-butyl lithium, hexyl lithium, phenyl lithium, stilbene lithium, dialkylamino lithium, diphenylamino lithium, and ditrimethylsilylamino lithium; organic dilithium compounds such as methylene dilithium, tetramethylene dilithium, hexamethylene dilithium, isoprenyl dilithium, and 1,4-dilithio-ethylcyclohexane; and organic trilithium compounds such as 1,3,5-trilithiobenzene; and the like.Among these, organic monolithium compounds are particularly preferably used.

[0043] Examples of the organic alkaline earth metal compounds include n-butyl magnesium bromide, n-hexyl magnesium bromide, ethoxy calcium, calcium stearate, t-butoxy strontium, ethoxy barium, isopropoxy barium, ethylmercapto barium, t-butoxy barium, phenoxy barium, diethylamino barium, barium stearate, and ethyl barium.

[0044] In addition to the above, a composite catalyst consisting of a lanthanoid series rare earth metal compound containing neodymium, samarium, gadolinium, etc. / alkylaluminum / alkylaluminum halide / alkylaluminum hydride, or a metallocene type catalyst containing titanium, vanadium, samarium, gadolinium, etc., which becomes a homogeneous system in an organic solvent and has living polymerizability, can also be used.

[0045] The polymerization initiator may be used alone or in combination of two or more. The amount of the polymerization initiator used may be determined according to the molecular weight of each target block copolymer and is not particularly limited, but is preferably 0.01 to 20 mmol, more preferably 0.05 to 15 mmol, and further preferably 0.1 to 10 mmol per 100 g of the total monomers used in the polymerization.

[0046] The solvent used in the polymerization is not particularly limited as long as it is inactive against the polymerization initiator, and examples thereof include chain hydrocarbon solvents, cyclic hydrocarbon solvents, and mixed solvents thereof. Examples of the chain hydrocarbon solvent include chain alkanes and alkenes having 4 to 6 carbon atoms, such as n-butane, isobutane, 1-butene, isobutylene, trans-2-butene, cis-2-butene, 1-pentene, trans-2-pentene, cis-2-pentene, n-pentane, isopentane, neo-pentane, and n-hexane. Examples of the cyclic hydrocarbon solvent include aromatic compounds such as benzene, toluene, and xylene; alicyclic hydrocarbon compounds such as cyclopentane and cyclohexane; and the like. These solvents may be used alone or in combination of two or more.

[0047] The amount of the solvent used is not particularly limited, but is preferably an amount such that the concentration of the total block copolymer in the solution after the polymerization reaction is 5 to 60% by weight, more preferably 10 to 55% by weight, and even more preferably 20 to 50% by weight.

[0048] In addition, during polymerization, a Lewis base compound may be added to the reaction system in order to control the structure of each polymer block of each block copolymer. Examples of the Lewis base compound include ethers such as tetrahydrofuran, diethyl ether, dioxane, ethylene glycol dimethyl ether, ethylene glycol dibutyl ether, diethylene glycol dimethyl ether, and diethylene glycol dibutyl ether; tertiary amines such as tetramethylethylenediamine, trimethylamine, triethylamine, pyridine, and quinuclidine; alkali metal alkoxides such as potassium t-amyl oxide and potassium t-butyl oxide; and phosphines such as triphenylphosphine. These Lewis base compounds may be used alone or in combination of two or more.

[0049] The timing of adding the Lewis base compound is not particularly limited, and may be appropriately determined according to the structure of each target block copolymer. For example, it may be added in advance before starting polymerization, or after some polymer blocks are polymerized. Furthermore, it may be added in advance before starting polymerization, and then additionally added after some polymer blocks are polymerized.

[0050] The polymerization reaction temperature is preferably 10 to 150° C., more preferably 30 to 130° C., and further preferably 40 to 90° C., and the polymerization time is preferably within 48 hours, more preferably 0.5 to 10 hours. The polymerization pressure is not particularly limited as long as it is within a pressure range sufficient to maintain the monomer and the solvent in a liquid phase at the polymerization temperature.

[0051] Under the above-mentioned conditions, an aromatic vinyl monomer is polymerized in a solvent using a polymerization initiator, whereby a solution containing an aromatic vinyl polymer having an active terminal can be obtained.

[0052] <Process (2)> Next, in step (2), a conjugated diene monomer is added to the solution containing the aromatic vinyl polymer having active ends obtained in step (1) above, and the conjugated diene monomer is polymerized to obtain a solution containing an aromatic vinyl-conjugated diene block copolymer having active ends.

[0053] According to the step (2), by adding a conjugated diene monomer to the solution containing the aromatic vinyl polymer having active ends obtained in the above step (1), a conjugated diene polymer chain is formed starting from the active end, and thus a solution containing an aromatic vinyl-conjugated diene block copolymer having active ends can be obtained.

[0054] <Process (3)> In step (3), a coupling agent is added to the solution containing the aromatic vinyl-conjugated diene block copolymer having active ends obtained in step (2) in an amount such that the total amount of functional groups relative to the active ends is less than 1 molar equivalent, and a part of the aromatic vinyl-conjugated diene block copolymer having active ends is coupled to obtain a solution containing a diblock copolymer component (A1) and a triblock copolymer component (A2).

[0055] The bifunctional coupling agent is not particularly limited as long as it has two functional groups that react with the active terminal, and examples thereof include bifunctional halogenated silanes such as dichlorosilane, monomethyldichlorosilane, and dimethyldichlorosilane; bifunctional halogenated alkanes such as dichloroethane, dibromoethane, methylene chloride, and dibromomethane; and bifunctional tin halides such as dichlorotin, monomethyldichlorotin, dimethyldichlorotin, monoethyldichlorotin, diethyldichlorotin, monobutyldichlorotin, and dibutyldichlorotin. These coupling agents may be used alone or in combination of two or more.

[0056] The amount of the bifunctional coupling agent used may be determined according to the ratio of the diblock copolymer component (A1) and the triblock copolymer component (A2).

[0057] <Process (4)> Next, in step (4), a block copolymer (A) containing a diblock copolymer component (A1) and a triblock copolymer component (A2) is recovered from the solution containing the diblock copolymer component (A1) and the block copolymer component (A2) obtained in the above step (3).

[0058] The recovery method may be any conventional method and is not particularly limited. For example, after the reaction is completed, if necessary, a polymerization terminator is added to deactivate the active end of the polymer having an active end, and if necessary, an additive such as an antioxidant is added, and then the solution is directly dried or subjected to a known solvent method such as steam stripping to recover the target block copolymer (A).

[0059] The polymerization terminator is not particularly limited as long as it can react with the active terminal to deactivate the active terminal, but is preferably a compound that does not contain a halogen atom, and is particularly preferably a polymerization terminator that generates a metal alkoxide, a metal aryloxide, or a metal hydroxide when reacting with the active terminal. Specific examples of the polymerization terminator include water; monohydric alcohols such as methanol and ethanol; monohydric phenols such as phenol and cresol; and the like.

[0060] When the block copolymer (A) is recovered as a slurry by steam stripping or the like, it is preferable to dehydrate the slurry using an arbitrary dehydrator such as an extruder-type squeezer to recover the block copolymer (A) in the form of crumbs, and further to dry the obtained crumbs using an arbitrary dryer such as a band dryer or an expansion extrusion dryer.

[0061] When the block copolymer (A) contains an aromatic vinyl-conjugated diene-aromatic vinyl triblock copolymer component (A3) represented by Ar-D-Ar, it can be produced by the following method.

[0062] That is, the block copolymer (A) can be produced by a production method including the following steps (1a) to (4a). (1a): A step of polymerizing an aromatic vinyl monomer in a solvent using a polymerization initiator to obtain a solution containing an aromatic vinyl polymer having an active terminal. (2a): A step of adding a conjugated diene monomer to the solution containing the aromatic vinyl polymer having active terminals obtained in the above step (1a) and polymerizing the conjugated diene monomer to obtain a solution containing an aromatic vinyl-conjugated diene block copolymer having active terminals. (3a): A step of adding an aromatic vinyl monomer to a solution containing an aromatic vinyl-conjugated diene block copolymer having an active terminal obtained in the above step (2) and polymerizing the aromatic vinyl monomer to obtain a solution containing a triblock copolymer component (A3). (4a): A step of recovering a block copolymer (A) containing the triblock copolymer component (A3) from the solution containing the triblock copolymer component (A3) obtained in the above step (3a).

[0063] <Process (1a), Process (2a)> Step (1a) and step (2a) are similar to the above-mentioned step (1) and step (2), and similar conditions can be employed.

[0064] <Process (3a)> In step (3a), an aromatic vinyl monomer is added to the solution containing the aromatic vinyl-conjugated diene block copolymer having an active end obtained in step (2a) above, and the aromatic vinyl monomer is polymerized to obtain a solution containing a triblock copolymer component (A3).

[0065] In this case, the polymerization conditions in step (3a), including the amount of the aromatic vinyl monomer, may be determined depending on the target weight average molecular weight of the aromatic vinyl polymer block to be formed (for example, the polymerization conditions may be determined within the ranges explained in the above step (1)).

[0066] <Process (4a)> Then, the block copolymer (A) containing the triblock copolymer component (A3) can be obtained by recovering the block copolymer (A) containing the triblock copolymer component (A3) from the solution containing the triblock copolymer component (A3) obtained in the step (3a). The step (4a) is the same as the above-mentioned step (4), and the same conditions can be used.

[0067] The block copolymer (A) is a mixture of an aromatic vinyl-conjugated diene diblock copolymer component (A1) represented by Ar-D and an aromatic vinyl-conjugated diene diblock copolymer component (A2) represented by Ar-D. n In the case where the copolymer contains an aromatic vinyl-conjugated diene-aromatic vinyl branched block copolymer component (A4) represented by -X (n is 3 or more), in the production method having the above steps (1) to (4), a method of using a trifunctional or higher functional coupling agent instead of a bifunctional coupling agent in the above step (3) may be adopted.

[0068] Examples of trifunctional coupling agents include trifunctional halogenated alkanes such as trichloroethane and trichloropropane; trifunctional halogenated silanes such as methyltrichlorosilane and ethyltrichlorosilane; trifunctional alkoxysilanes such as methyltrimethoxysilane, phenyltrimethoxysilane, and phenyltriethoxysilane; and the like. Examples of tetrafunctional coupling agents include tetrafunctional halogenated alkanes such as carbon tetrachloride, carbon tetrabromide, and tetrachloroethane; tetrafunctional halogenated silanes such as tetrachlorosilane and tetrabromosilane; tetrafunctional alkoxysilanes such as tetramethoxysilane and tetraethoxysilane; tetrafunctional tin halides such as tetrachlorotin and tetrabromostin; and the like. Examples of pentafunctional or higher coupling agents include 1,1,1,2,2-pentachloroethane, perchloroethane, pentachlorobenzene, perchlorobenzene, octabromodiphenyl ether, and decabromodiphenyl ether. These coupling agents may be used alone or in combination of two or more.

[0069] <Pellet Molded Product of Block Copolymer (A)> The pellet-shaped product of the block copolymer (A) used in the present invention can be obtained by pelletizing the block copolymer (A). The pelletization can be carried out by using a conventionally known method. For example, the block copolymer (A) is extruded in a strand shape from a single-screw extruder or a twin-screw extruder, cooled with water or air, and then cut with a strand cutter; a rotary blade is installed in front of the die of the single-screw extruder or twin-screw extruder, and the strand-shaped block copolymer (A) immediately after being extruded from the die is cut in a water flow or underwater; a method in which the block copolymer (A) is melt-mixed with an open roll or a bumper mixer, formed into a sheet shape with a roll, the sheet is cut into strips, and then cut into cubic pellets with a pelletizer; and the like. The size and shape of the pellet-shaped product of the block copolymer (A) are not particularly limited.

[0070] The pellet-shaped product of the block copolymer (A) may be a pellet-shaped product or a crumb-shaped product.

[0071] The pellet molded product of the block copolymer (A) preferably contains a polystyrene polymer in addition to the block copolymer (A). By containing a polystyrene polymer in addition to the block copolymer (A), the blocking resistance can be further improved.

[0072] The polystyrene polymer may be any polymer constituted mainly of repeating units that are styrene units obtained by polymerizing styrene, and the content of styrene units in the polystyrene polymer is preferably 80% by weight or more, more preferably 90% by weight or more, and particularly preferably substantially 100% by weight.

[0073] The polystyrene polymer may contain a unit of a monomer other than the styrene unit, and examples of such a monomer include aromatic vinyl monomers other than styrene and monomers other than aromatic vinyl. Examples of aromatic vinyl monomers other than styrene include styrenes having an alkyl group as a substituent, such as α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2,4-diisopropylstyrene, 2,4-dimethylstyrene, 4-t-butylstyrene, and 5-t-butyl-2-methylstyrene; styrenes having a halogen atom as a substituent, such as 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, 4-bromostyrene, and 2,4-dibromostyrene; styrenes having an alkyl group and a halogen atom as a substituent, such as 2-methyl-4,6-dichlorostyrene; vinylnaphthalene; and the like. Examples of monomers other than aromatic vinyl include conjugated diene monomers such as 1,3-butadiene and isoprene (2-methyl-1,3-butadiene); α,β-unsaturated nitrile monomers such as acrylonitrile and methacrylonitrile; unsaturated carboxylic acid monomers such as acrylic acid, methacrylic acid, maleic acid, fumaric acid, and itaconic acid; unsaturated carboxylic acid anhydrides such as maleic anhydride, butenyl succinic anhydride, tetrahydrophthalic anhydride, and citraconic anhydride; unsaturated carboxylic acid ester monomers such as methyl acrylate, ethyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, and 2-ethylhexyl methacrylate; and non-conjugated diene monomers preferably having 5 to 12 carbon atoms, such as 1,4-pentadiene and 1,4-hexadiene.

[0074] The content of the polystyrene polymer in the pellet molded product is preferably 0.5 to 5.0 parts by weight, more preferably 0.6 to 4.5 parts by weight, and even more preferably 1.0 to 4.0 parts by weight, based on 100 parts by weight of the block copolymer (A). By setting the content of the polystyrene polymer within the above range, it is possible to more appropriately improve the blocking resistance while suppressing the decrease in transparency. If the content of the polystyrene polymer is too small, it becomes difficult to obtain the effect of improving the blocking resistance, while if it is too large, the transparency may decrease. The molecular weight of the polystyrene polymer is not particularly limited, but the number average molecular weight (Mn) is preferably 1,000 to 500,000, more preferably 5,000 to 100,000, and even more preferably 6,000 to 30,000.

[0075] The method for making the pellet molded body contain a polystyrene polymer in addition to the block copolymer (A) is not particularly limited, but includes a method in which, when producing the block copolymer (A), a polymerization terminator is added according to the amount of the polystyrene polymer to be blended after the above-mentioned step (1) or step (1a) to obtain a block copolymer (A) containing a polystyrene polymer, which is then pelletized. Alternatively, a method can be adopted in which a polystyrene polymer polymer polymerized separately is added to the block copolymer (A), and the two are mixed, and then pelletized according to the above-mentioned method.

[0076] <Hydrocarbon dusting agent (B)> The hydrocarbon-based dusting agent (B) used in the present invention is a dusting agent made of a hydrocarbon-based powder and has a specific surface area of ​​0.50 to 3.00 m. 2 / g, volume average particle size is 2.0 to 20 μm, bulk density is 0.10 to 0.34 g / cm 3 and has a melting point of 75°C or higher.

[0077] In the present invention, such a hydrocarbon-based dusting agent (B) is combined with the pellet molding of the above-mentioned block copolymer (A) to form the block copolymer pellets, and the Shore A hardness and BET specific surface area of ​​the block copolymer pellets are set within the specific ranges described below, so that the block copolymer pellets are suppressed from causing dusting, have excellent blocking resistance and transparency, and exhibit high adhesion to adherends.

[0078] The hydrocarbon powder constituting the hydrocarbon-based dusting agent (B) is not particularly limited as long as it is made of a hydrocarbon compound, but from the viewpoint of further enhancing the effect of the present invention, it is preferable that it is a powder of a compound consisting essentially of carbon and hydrogen, and more preferably a polyolefin-based powder such as polyethylene or polypropylene.

[0079] The hydrocarbon dusting agent (B) used in the present invention has a BET specific surface area of ​​0.50 to 3.00 m 2 / g, preferably 0.8 to 2.5 m 2 / g, more preferably 1.0 to 2.3 m 2 / g. If the BET specific surface area is too small, the block copolymer pellets obtained will have poor blocking resistance, while if the BET specific surface area is too large, dusting will occur easily. The BET specific surface area of ​​the hydrocarbon dusting agent (B) can be determined by the Kr adsorption method, that is, by measuring the gas adsorption amount by a volumetric method using krypton (Kr) gas as the adsorbed gas, and calculating the specific surface area by the BET method. When two or more types of dusting agents with different BET specific surface areas are used as the dusting agent (B), the average value of the BET specific surface area taking into account the blending amounts of the two or more types of dusting agents may be set to the above range.

[0080] The volume average particle diameter of the hydrocarbon-based dusting agent (B) used in the present invention is 2.0 to 20 μm, preferably 5 to 19 μm, and more preferably 8 to 18 μm. If the volume average particle diameter is too small, dusting is likely to occur, while if the volume average particle diameter is too large, the resulting block copolymer pellets will have poor blocking resistance. The volume average particle diameter of the hydrocarbon-based dusting agent (B) can be determined by dispersing the hydrocarbon-based dusting agent (B) in isopropanol and measuring it with a laser diffraction / scattering type particle size distribution measuring device. When two or more types of dusting agents with different volume average particle diameters are used as the dusting agent (B), the average value of the volume average particle diameter taking into account the blending amounts of the two or more types of dusting agents may be set to the above range.

[0081] The hydrocarbon dusting agent (B) used in the present invention has a bulk density of 0.10 to 0.34 g / cm 3 and preferably 0.12 to 0.30 g / cm 3 , more preferably 0.16 to 0.26 g / cm 3 If the bulk density of the hydrocarbon-based dusting agent (B) is too low, the block copolymer pellets obtained are prone to dusting and have poor blocking resistance. On the other hand, if the bulk density of the hydrocarbon-based dusting agent (B) is too high, the block copolymer pellets obtained have poor blocking resistance. When two or more types of dusting agents with different bulk densities are used as the dusting agent (B), the average bulk density taking into account the blending amounts of the two or more types of dusting agents may be set to the above range.

[0082] Furthermore, the hydrocarbon dusting agent (B) used in the present invention has a melting point of 75° C. or higher, preferably 90 to 170° C., and more preferably 100 to 170° C. If the melting point of the hydrocarbon dusting agent (B) is too low, the resulting block copolymer pellets will have poor blocking resistance.

[0083] In addition, the hydrocarbon-based dusting agent (B) used in the present invention preferably contains particles having a particle diameter of 20 μm or more at a ratio of 3 to 40% by volume, and more preferably contains particles having a particle diameter of 20 μm or more at a ratio of 5 to 25% by volume, from the viewpoint of being able to further improve the blocking resistance of the resulting block copolymer pellets. The ratio of particles having a particle diameter of 20 μm or more in the hydrocarbon-based dusting agent (B) can be determined by dispersing the hydrocarbon-based dusting agent (B) in isopropanol and measuring it with a laser diffraction / scattering type particle size distribution measuring device. When two or more types of dusting agents are used as the dusting agent (B), the ratio of particles having a particle diameter of 20 μm or more to the total amount of the two or more types of dusting agents may be within the above range.

[0084] <Block copolymer pellets> The block copolymer pellets of the present invention contain 100 parts by weight of the pellet molded product of the block copolymer (A) described above and 0.01 to 5 parts by weight of the hydrocarbon dusting agent (B) described above, and have a Shore A hardness of 10 to 80 and a BET specific surface area measured by the Kr adsorption method of 0.001 to 0.05 m. 2 / g.

[0085] According to the present invention, the block copolymer pellets are a combination of the pellet molded body of the block copolymer (A) described above and the hydrocarbon-based dusting agent (B) described above, and the Shore A hardness and BET specific surface area thereof are within the above-mentioned ranges, thereby suppressing dusting, providing excellent blocking resistance and transparency, and exhibiting high adhesion to the adherend.

[0086] In the block copolymer pellets of the present invention, the amount of the hydrocarbon dusting agent (B) relative to 100 parts by weight of the block copolymer pellets is 0.01 to 5 parts by weight, preferably 0.05 to 4.2 parts by weight, more preferably 0.1 to 3.2 parts by weight, and even more preferably 0.2 to 0.5 parts by weight. If the amount of the hydrocarbon dusting agent (B) is too small, the block copolymer pellets will have poor blocking resistance. On the other hand, if the amount of the hydrocarbon dusting agent (B) is too large, the block copolymer pellets will tend to be dusty.

[0087] There is no particular limitation on the method of mixing the pellets of the block copolymer (A) and the hydrocarbon-based dusting agent (B), and examples of the method include a method of mixing the two in a mixer such as a tumbler; a method of dispersing the hydrocarbon-based dusting agent (B) in water using a surfactant as necessary, and contacting the aqueous dispersion of the hydrocarbon-based dusting agent (B) with the pellets of the block copolymer (A); a method of adding an aqueous dispersion of the hydrocarbon-based dusting agent (B) prepared in the same manner as above to the cooling water in the process of extruding the block copolymer (A) in a strand shape from an extruder, cooling with water, and cutting with a strand cutter; etc. The processing temperature in this case is preferably 5 to 50°C, more preferably 10 to 30°C.

[0088] The Shore A hardness of the block copolymer pellet of the present invention is 10 to 80, preferably 20 to 70, more preferably 25 to 67, and even more preferably 30 to 65. If the Shore A hardness is too low, the blocking resistance will be poor. On the other hand, if the Shore A hardness is too high, good adhesive properties cannot be obtained. The Shore A hardness of the block copolymer pellet can be adjusted, for example, by adjusting the monomer composition of the polymer components constituting the block copolymer (A) or by adjusting the composition of the diblock polymer and triblock polymer.

[0089] Furthermore, the BET specific surface area of ​​the block copolymer pellets of the present invention measured by the Kr adsorption method is 0.001 to 0.05 m 2 / g, preferably 0.005 to 0.04 m 2 / g, more preferably 0.01 to 0.03 m 2 / g. If the BET specific surface area of ​​the block copolymer pellets is too small, the blocking resistance will be poor. On the other hand, if the BET specific surface area is too large, the blocking resistance will be poor. The BET specific surface area of ​​the block copolymer pellets can be determined by the Kr adsorption method, that is, by measuring the gas adsorption amount by a volumetric method using krypton (Kr) gas as the adsorption gas, and calculating the specific surface area by the BET method. The BET specific surface area of ​​the block copolymer pellets can be adjusted, for example, by adjusting the BET specific surface area of ​​the hydrocarbon dusting agent (B) or by adjusting the resin temperature when the block copolymer (A) is molded into pellets by melt extrusion molding.

[0090] <Adhesive composition> The pressure-sensitive adhesive composition of the present invention is obtained by using the block copolymer pellets described above. Since the pressure-sensitive adhesive composition of the present invention is obtained by using the block copolymer pellets described above, it has excellent adhesion properties to adherends.

[0091] The pressure-sensitive adhesive composition of the present invention may be one obtained by using the block copolymer pellets described above. For example, the pressure-sensitive adhesive composition may be one obtained by using a tackifier resin in addition to the block copolymer pellets described above.

[0092]

[0113] As the tackifier resin, those generally used in pressure-sensitive adhesive compositions can be used, and are not particularly limited. For example, rosin; modified rosins such as disproportionated rosin and dimerized rosin; esters of polyhydric alcohols such as glycol, glycerin and pentaerythritol with rosin or modified rosins; terpene resins; aliphatic, aromatic, alicyclic or aliphatic-aromatic copolymer hydrocarbon resins such as petroleum resins or hydrogenated versions thereof; phenolic resins; coumarone-indene resins, and the like can be used as the tackifier resin. Among these, aliphatic, aromatic, alicyclic or aliphatic-aromatic copolymer hydrocarbon resins or hydrogenated versions thereof are preferably used.

[0093] The blending ratio of the block copolymer pellets and the tackifier resin may be appropriately adjusted depending on the application of the pressure-sensitive adhesive composition, but the blending amount of the tackifier resin is preferably 5 to 6000 parts by weight, more preferably 40 to 4500 parts by weight, relative to 100 parts by weight of the block copolymer pellets.

[0094] The adhesive composition of the present invention may contain various additives such as a softener, a plasticizer, an antioxidant, a filler, a lubricant, etc., as necessary.

[0095] The adhesive composition of the present invention can be prepared according to the same method as that of a general adhesive composition. For example, block copolymer pellets, a tackifier resin, and additives used as needed can be stirred and mixed in the presence of a solvent to form an adhesive solution. The adhesive solution thus obtained is usually uniformly applied to a desired substrate using a coating machine, dried, and then wound up to form various adhesive tapes or adhesive label products. Alternatively, block copolymer pellets, a tackifier resin, and additives used as needed can be simultaneously or sequentially charged into a melting pot from the one with the lowest melt viscosity, and heated and melted at 100 to 200 ° C., and then processed into an appropriate shape such as a block, rod, powder, film, or sheet, or can be continuously produced using a single-screw or twin-screw extruder.

[0096] <Stretchable film> The stretch film of the present invention is a stretchable film obtained by using the block copolymer pellets described above. The stretchable film of the present invention is obtained by using the block copolymer pellets described above, and therefore has excellent stretchability.

[0097] The stretchable film of the present invention may contain polymer components and additives other than the block copolymer pellets described above. Examples of polymer components other than the block copolymer pellets described above include olefin resins such as polyethylene and polypropylene, and styrene resins such as polystyrene and impact-resistant polystyrene. Examples of polymer components other than the block copolymer pellets described above include conjugated diene homopolymers, aromatic vinyl-conjugated diene random copolymers, and branched polymers thereof; thermoplastic elastomers such as polyurethane thermoplastic elastomers, polyamide thermoplastic elastomers, and polyester thermoplastic elastomers; thermoplastic resins such as polyvinyl chloride, acrylonitrile-styrene copolymers, acrylonitrile-butadiene-styrene copolymers, and polyphenylene ether; and the like.

[0098] Furthermore, the stretchable film of the present invention may contain various additives, such as antioxidants, tackifier resins, softeners, antibacterial agents, light stabilizers, ultraviolet absorbers, dyes, pigments, and lubricants, as necessary.

[0099] The method of mixing the block copolymer pellets with other components is not particularly limited. For example, the block copolymer pellets may be mixed with other polymer components and various additives as necessary, and then mixed according to a conventional method such as kneading or solution mixing. Specifically, each component may be dissolved in a solvent and mixed uniformly, and then the solvent may be removed by heating, or each component may be melt-mixed using a screw extruder or kneader. Among these, melt mixing is preferred from the viewpoint of more efficient mixing. The temperature at which melt mixing is performed is not particularly limited, but is usually in the range of 100 to 200°C.

[0100] The thickness of the stretchable film is not particularly limited and may be adjusted depending on the application. For example, when the stretchable film is used as a film for sanitary products such as disposable diapers and sanitary products, the thickness of the stretchable film is usually 0.01 to 5 mm, preferably 0.01 to 1 mm, and more preferably 0.02 to 0.2 mm.

[0101] The method of forming the block copolymer pellets into a film is not particularly limited, and a conventionally known film forming method can be applied, but from the viewpoint of obtaining a smooth film with good productivity, extrusion molding is preferable, and among them, extrusion molding using a T-die is particularly preferable. A specific example of extrusion molding using a T-die is a method in which a film composition molten at 150 to 250 ° C. is extruded from a T-die attached to a single-screw extruder or a twin-screw extruder, and is wound up while being cooled with a take-up roll. When cooling with a take-up roll, the film may be stretched. In addition, when winding the film, a melt of the film composition containing the block copolymer pellets may be coated on a substrate made of polyethylene terephthalate, polyethylene, polypropylene, nonwoven fabric or release paper to form a film, or a melt of the film composition containing the block copolymer pellets may be sandwiched between these substrates to form a film. The film obtained in this way may be used as it is in a form integrated with the substrate, or may be peeled off from the substrate.

[0102] The stretchable film of the present invention can be used as a single layer or can be laminated with other members to form a multilayer body depending on the application. Specific examples of the use of the film as a single layer include stretchable films used in sanitary products such as paper diapers and sanitary products, protective films for protecting optical films, and heat-shrinkable films used for shrink packaging of containers and heat-shrinkable labels. Specific examples of the use of the film as a multilayer body include a case in which the film of the present invention is slit and then coated with a hot melt adhesive or the like to form a tape, and the tape is attached in a shrunk state to a nonwoven fabric, a woven fabric, a plastic film, or a laminate of these, and the shrinkage of the tape is relaxed to form a stretchable gather member. Furthermore, the film can be appropriately processed according to a known method depending on other applications, and can be used as a stretchable member such as a base material for stretchable patches, gloves, surgical gloves, finger cots, tourniquets, contraceptives, headbands, goggle bands, and rubber bands. EXAMPLES

[0103] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. Note that "parts" and "%" are by weight unless otherwise specified. The test methods used in the present examples and comparative examples are as follows.

[0104] [Weight average molecular weight] The molecular weight was calculated as polystyrene equivalent molecular weight by high performance liquid chromatography using tetrahydrofuran as a carrier at a flow rate of 0.35 ml / min. The apparatus used was a Tosoh HLC8320, the column was a combination of three Showa Denko Shodex (registered trademark) KF-404HQ columns (column temperature 40°C), and the detectors were a differential refractometer and an ultraviolet detector. The molecular weight was calibrated with 12 standard polystyrene points (5 to 3 million) from Polymer Laboratory.

[0105] [Weight ratio of each block copolymer component in the block copolymer] The ratio was determined from the area ratio of the peaks corresponding to each block copolymer in the chart obtained by the above-mentioned high performance liquid chromatography.

[0106] [Weight average molecular weight of styrene polymer block in each polymer component] According to the method described in Rubber Chem. Technol., 45, 1295 (1972), the isoprene polymer block of the block copolymer was decomposed by reacting the block copolymer with ozone and reducing it with lithium aluminum hydride. Specifically, the following procedure was followed. That is, 300 mg of the sample was dissolved in a reaction vessel containing 100 ml of dichloromethane treated with molecular sieves. After placing this reaction vessel in a cooling bath and lowering the temperature to -25°C, ozone generated by an ozone generator was introduced into the reaction vessel while oxygen was flowing at a flow rate of 170 ml / min. After 30 minutes had passed since the start of the reaction, the reaction was confirmed to be complete by introducing the gas flowing out of the reaction vessel into the potassium iodide aqueous solution. Next, 50 ml of diethyl ether and 470 mg of lithium aluminum hydride were charged into another reaction vessel substituted with nitrogen, and the solution reacted with ozone was slowly dropped into the reaction vessel while cooling the reaction vessel with ice water. Then, the reaction vessel was placed in a water bath, gradually heated, and refluxed at 40°C for 30 minutes. After that, while stirring the solution, dilute hydrochloric acid was dropped into the reaction vessel in small amounts until almost no hydrogen was generated. After the reaction, the solid product generated in the solution was filtered, and the solid product was extracted with 100 ml of diethyl ether for 10 minutes. The extract and the filtrate were combined, and the solvent was distilled off to obtain a solid sample. The weight average molecular weight of the sample thus obtained was measured according to the above-mentioned method for measuring weight average molecular weight, and the value was taken as the weight average molecular weight of the styrene polymer block.

[0107] [Weight average molecular weight of isoprene polymer block in each polymer component] The weight average molecular weight of the corresponding styrene polymer block was subtracted from the weight average molecular weight of the block copolymer obtained as above, and the weight average molecular weight of the isoprene polymer block was calculated based on the calculated value.

[0108] [Styrene unit content in each polymer component] The value was determined based on the ratio of the detection intensities of the differential refractometer and the ultraviolet detector in the measurement by high performance liquid chromatography. Note that copolymers having different styrene unit contents were prepared in advance, and a calibration curve was prepared using them.

[0109] [Styrene unit content in block copolymer] 1 It was determined based on H-NMR measurement.

[0110] [Vinyl bond content of isoprene polymer block] 1 It was determined based on H-NMR measurement.

[0111] [Shore A hardness of block copolymer pellets] The Shore A hardness of the block copolymer pellets was determined in accordance with ISO 7619. The details are as follows. 15 g of block copolymer pellets were placed in a press molding machine set at 170° C., premelted for 1 minute under pressure of 0.1 to 0.5 MPa, and then molded into a sheet under pressure of 20 MPa. This operation was repeated 2 to 3 times to produce a uniform sheet. The obtained sheet was folded to a size of 4 cm x 4 cm, then placed again in the press molding machine using a 2 mm thick mold, pre-melted for 1 minute under a pressure of 0.1 to 0.5 MPa, and then molded into a 2 mm thick plate by applying a pressure of 10 MPa. The obtained plate-like sample was cut into a size of 3 cm x 4 cm, and three of these were stacked together to prepare a sample for hardness measurement. A durometer (type A) was used for the measurement. The sample for hardness measurement was placed in a designated location, the measuring needle was slowly lowered onto the sample, and the reading was read 10 seconds after the needle was lowered. Measurements were taken 5 times at different measurement positions, and the average value was calculated.

[0112] [BET specific surface area of ​​block copolymer pellets] The BET specific surface area of ​​the block copolymer pellets was determined by measuring the gas adsorption amount by a volumetric method using krypton (Kr) gas as the adsorption gas, and calculating the specific surface area by the BET method.

[0113] [Blocking Resistance of Block Copolymer Pellet] The blocking resistance of the block copolymer pellets was evaluated by placing 50 g of block copolymer pellets in a 100 mm x 100 mm vinyl bag, sealing the opening of the bag tightly with cellophane tape, placing it in an oven set at 60°C, placing a SUS plate and a 5 kg weight on top of it, and leaving it for 10 hours. After that, visually checking whether the pellets were blocking each other, the block copolymer pellets ◎◎: The area of ​​the blocking portion is 0% of the total area. ◎: The area of ​​the blocking portion is more than 0% and 10% or less of the total area. ○: The area of ​​the blocking portion is more than 10% and less than 20% of the total area. ×: The area of ​​the blocked portion is more than 20% of the total area.

[0114] [Block copolymer pellet dust] 3 kg of block copolymer pellets were sealed in a polyethylene bag and shaken 30 times. Next, a transparent acrylic case (length 30 cm, width 10 cm, height 10 cm) with a lid that can be opened and closed was placed in the bag, and the air layer was collected in the acrylic case. A white piece of paper with a cross printed on it was placed on a laboratory bench, and a transparent acrylic case was placed on top of it with its length facing up and down. The cross was visually observed through the acrylic case, and the degree of powdering was evaluated based on whether the outline could be clearly identified. ○: Character outlines are clearly distinguishable (little dusting) ×: Character outlines are not clearly distinguishable (lots of dust)

[0115] [Transparency of Block Copolymer Pellet] A 1 mm thick press sheet was prepared from the block copolymer pellets, and the light transmittance at 550 nm was measured using an ultraviolet-visible spectrophotometer. ○: Transmittance ≧70% ×: Transmittance <70%

[0116] [Odor of block copolymer pellets] The odor of the block copolymer pellets was evaluated by a sensory test. Specifically, 50 g of the block copolymer pellets were placed in a 300 ml heat-resistant container and covered with aluminum foil. The heat-resistant container containing the block copolymer pellets was then placed in an oven and heated at 150°C for 30 minutes, and the odor after heating was confirmed. The odor was confirmed by a panel of six people who were not accustomed to the odor of organic compounds (i.e., who do not come into contact with the odor of organic compounds in their daily lives), and was evaluated according to the following criteria. 0: Odorless 1: A barely detectable odor 2: A weak odor that makes it easy to tell what it is. 3. Easily detectable odors 4: Strong odor 5: Strong odor The average scores of the six panelists were then calculated and evaluated according to the following criteria. ○: Odor intensity <3 ×: Odor intensity ≧3

[0117] [Peel adhesion strength of adhesive composition (N / 25 mm)] The adhesive sheets prepared using the adhesive compositions were measured for peel adhesion strength (N / 25 mm) at 23°C using a polyethylene substrate as an adherend in accordance with PSTC-1 (180° peel adhesion test by the Pressure Sensitive Tape Committee (USA)), and evaluated according to the following criteria. ○: Peel adhesion strength is 2.0N / 25mm or more ×: Peel adhesion strength is less than 2.0N / 25mm

[0118] [Production Example 1] (Production of Block Copolymer (A-1)) In a pressure-resistant reactor, 23.3 kg of cyclohexane, 1.5 mmol of N,N,N',N'-tetramethylethylenediamine (hereinafter referred to as TMEDA), and 1.2 kg of styrene were added, and while stirring at 40°C, 101.7 mmol of n-butyllithium was added, and polymerization was carried out for 1 hour while raising the temperature to 50°C. The polymerization conversion rate of styrene was 100% by weight. Subsequently, 6.53 kg of isoprene was continuously added to the reactor over 1 hour while controlling the temperature to maintain 50-60°C. After the addition of isoprene was completed, polymerization was continued for another 1 hour to form a styrene-isoprene diblock copolymer component represented by Ar-D. The polymerization conversion rate of isoprene was 100%. Next, 37.6 mmol of dimethyldichlorosilane was added as a coupling agent to carry out a coupling reaction for 2 hours, and a styrene-isoprene-styrene triblock copolymer component represented by (Ar-D)2-X was formed. Thereafter, 203 mmol of methanol was added as a polymerization terminator and mixed thoroughly to stop the reaction. The amounts of each reagent used in the reaction are summarized in Table 1. A part of the obtained reaction solution was taken out, and the weight average molecular weight of each block copolymer component and the entire block copolymer, the weight ratio of each block copolymer in the block copolymer component, the weight average molecular weight of each styrene polymer block, the weight average molecular weight of each isoprene polymer block, the styrene unit content of each block copolymer component, the styrene unit content of the entire block copolymer, and the vinyl bond content of the isoprene polymer block were determined. These values ​​are shown in Table 2. 0.3 parts of 2,6-di-tert-butyl-p-cresol was added as an antioxidant to 100 parts of the reaction solution obtained as above (containing 30 parts of polymer component), and mixed, and the mixed solution was dropped into warm water heated to 85 to 95 ° C. in small amounts to volatilize the solvent and obtain a precipitate, which was then crushed and dried with hot air at 85 ° C. to recover the block copolymer (A-1) of Production Example 1. The melt index of the resulting block copolymer (A-1) was measured, and the melt index value is shown in Table 2.

[0119] [Production Example 2] (Production of Block Copolymer (A-2)) A block copolymer (A-2) of Production Example 2 was obtained in the same manner as in Production Example 1, except that the amounts of styrene, n-butyllithium, TMEDA, isoprene, dimethyldichlorosilane, and methanol were changed as shown in Table 1. In addition, the block copolymer (A-2) of Production Example 2 was subjected to the same measurements as in Production Example 1. The results are shown in Table 2.

[0120] [Production Example 3] (Production of Block Copolymer (A-3)) A block copolymer (A-3) of Production Example 3 was obtained in the same manner as in Production Example 1, except that the amounts of styrene, n-butyllithium, TMEDA, isoprene, and methanol were changed as shown in Table 1, and 27.6 mmol of tetramethoxysilane was used instead of dimethyldichlorosilane. In addition, the block copolymer (A-3) of Production Example 3 was subjected to the same measurements as in Production Example 1. The results are shown in Table 2.

[0121] [Production Example 4] (Production of Block Copolymer (A-4)) A block copolymer (A-4) of Production Example 4 was obtained in the same manner as in Production Example 1, except that the amounts of styrene, n-butyllithium, TMEDA, isoprene, dimethyldichlorosilane, and methanol were changed as shown in Table 1. In addition, the block copolymer (A-4) of Production Example 4 was subjected to the same measurements as in Production Example 1. The results are shown in Table 2.

[0122] [Production Example 5] (Production of Block Copolymer (A-5)) Into a pressure-resistant reactor, 23.3 kg of cyclohexane, 1.3 mmol of N,N,N',N'-tetramethylethylenediamine (hereinafter referred to as TMEDA), and 1.08 kg of styrene were added, and while stirring at 40°C, 87.0 mmol of n-butyllithium was added, and polymerization was carried out for 1 hour while raising the temperature to 50°C. The polymerization conversion rate of styrene was 100% by weight. Subsequently, 5.57 kg of isoprene was continuously added to the reactor over 1 hour while controlling the temperature to maintain 50-60°C. After the addition of isoprene was completed, polymerization was carried out for another 1 hour to form a styrene-isoprene diblock copolymer component represented by Ar-D. The polymerization conversion rate of isoprene was 100%. Next, 1.08 kg of styrene was continuously added to the reactor over 1 hour while controlling the temperature to maintain 50-60°C. After the addition of styrene was completed, polymerization was carried out for another 1 hour to form a styrene-isoprene-styrene diblock copolymer component represented by Ar-D-Ar. After this, 174 mmol of methanol was added as a polymerization terminator and mixed well to stop the reaction. The amounts of each reagent used in the reaction are summarized in Table 1. Then, a part of the obtained reaction liquid was taken out and each measurement was performed in the same manner as in Production Example 1. These values ​​are shown in Table 2. 0.3 parts of 2,6-di-tert-butyl-p-cresol was added as an antioxidant to 100 parts of the reaction liquid obtained as above (containing 30 parts of polymer component) and mixed, and the mixed solution was dropped into hot water heated to 85 to 95 ° C. in small amounts to volatilize the solvent and obtain a precipitate, which was crushed and dried with hot air at 85 ° C. to recover the block copolymer (A-5) of Production Example 5. The melt index of the obtained block copolymer (A-5) was measured. The melt index value is shown in Table 2.

[0123] [Table 1]

[0124] [Table 2]

[0125] Example 1 The block copolymer (A-1) obtained in Production Example 1 was fed into a twin-screw extruder, and the discharged strand was cooled in water at 10°C and then cut into 2.5 mm lengths using a pelletizer to obtain pellets of the block copolymer (A-1) having a diameter of 2.5 mm and a length of 2.5 mm. The molding temperature (resin temperature) of the twin-screw extruder was set to 215°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) obtained above and polyethylene powder (B-1) (BET specific surface area: 1.249 m) were mixed together. 2 / g, volume average particle size: 2.5 μm, bulk density: 0.13 g / cm 3 0.3 parts of polyethylene powder (B-1), melting point: 93°C, proportion of particles with a particle size of 20 μm or more: 0% by volume, were used and stirred in a Henschel mixer at room temperature for 2 minutes to obtain block copolymer pellets. The BET specific surface area of ​​the polyethylene powder (B-1) was determined by the Kr adsorption method, and the volume average particle size and proportion of particles with a particle size of 20 μm or more were determined by measurement using a laser diffraction / scattering type particle size distribution analyzer (the same applies to the following examples and comparative examples). Then, using the obtained block copolymer pellets, the Shore A hardness, BET specific surface area, blocking resistance, dustiness, transparency, and odor were measured and evaluated according to the above-mentioned methods. The results are shown in Table 3.

[0126] In addition, 50 parts of the block copolymer pellets obtained above, 50 parts of petroleum resin (trade name "Quintone R100", manufactured by Nippon Zeon Co., Ltd.), and 10 parts of oil (trade name "Naptone oil N100", manufactured by Nippon San Oil Co., Ltd.) were kneaded at 180°C for 1 hour to obtain a pressure-sensitive adhesive composition. The obtained pressure-sensitive adhesive composition was then melt-coated on a 25 μm-thick PET film to a thickness of 20 μm to prepare a pressure-sensitive adhesive sheet, and the peel adhesion strength was measured according to the method described above. The results are shown in Table 3.

[0127] Example 2 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 160°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and 0.3 parts of the polyethylene powder (B-1) was replaced with polypropylene powder (B-2) (BET specific surface area: 0.845 m 2 / g, volume average particle size: 5.5 μm, bulk density: 0.14 g / cm 3 Except for using 0.3 parts of 1,2-dichloromethane (1,2-dichloromethane), melting point: 155°C, and ratio of particles having a particle size of 20 μm or more: 0% by volume, block copolymer pellets and a pressure-sensitive adhesive sheet were prepared in the same manner as in Example 1, and evaluations were performed in the same manner. The results are shown in Table 3.

[0128] Example 3 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 230°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and 0.3 parts of the polyethylene powder (B-1) was replaced with polyethylene powder (B-3) (BET specific surface area: 2.228 m 2 / g, volume average particle size: 8.5 μm, bulk density: 0.25 g / cm 3 Except for using 0.3 parts of 1.0% by volume of particles having a particle size of 20 μm or more, melting point: 124° C., and a melting point of 124° C., the melting point of 1.0% by volume of particles having a particle size of 20 μm or more, the block copolymer pellets and the pressure-sensitive adhesive sheet were prepared in the same manner as in Example 1, and the evaluations were performed in the same manner. The results are shown in Table 3.

[0129] Example 4 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 200°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and polypropylene powder (B-4) (BET specific surface area: 1.523 m) was used in place of 0.3 parts of the polyethylene powder (B-1). 2 / g, volume average particle size: 9.5 μm, bulk density: 0.29 g / cm 3 Except for using 0.3 parts of 1,2-dichloromethane (II), melting point: 145°C, and ratio of particles having a particle size of 20 μm or more: 2.5% by volume, block copolymer pellets and a pressure-sensitive adhesive sheet were prepared in the same manner as in Example 1, and evaluated in the same manner. The results are shown in Table 3.

[0130] Example 5 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 240°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and 0.3 parts of the polyethylene powder (B-1) was replaced with polypropylene powder (B-5) (BET specific surface area: 0.958 m 2 / g, volume average particle size: 18 μm, bulk density: 0.25 g / cm 3 Except for using 0.3 parts of 1,2-dichloromethane (II), melting point: 116°C, and ratio of particles having a particle size of 20 μm or more: 45.0% by volume, block copolymer pellets and a pressure-sensitive adhesive sheet were prepared in the same manner as in Example 1, and evaluated in the same manner. The results are shown in Table 3.

[0131] Comparative Example 1 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 210°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and polyethylene powder (B-6) (BET specific surface area: 1.499 m) was used in place of 0.3 parts of the polyethylene powder (B-1). 2 / g, volume average particle size: 2.7 μm, bulk density: 0.08 g / cm3 Except for using 0.3 parts of 1,2-dichloromethane (1,2-dichloromethane), melting point: 140°C, and ratio of particles having a particle size of 20 μm or more: 0% by volume, block copolymer pellets and a pressure-sensitive adhesive sheet were prepared in the same manner as in Example 1, and evaluations were performed in the same manner. The results are shown in Table 3.

[0132] Comparative Example 2 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 170°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and polyethylene powder (B-7) (BET specific surface area: 3.539 m) was used in place of 0.3 parts of the polyethylene powder (B-1). 2 / g, volume average particle size: 3.5 μm, bulk density: 0.11 g / cm 3 Except for using 0.3 parts of 1,2-dichloromethane (1,2-dichloromethane), melting point: 93°C, and ratio of particles having a particle size of 20 μm or more: 0% by volume, block copolymer pellets and a pressure-sensitive adhesive sheet were prepared in the same manner as in Example 1, and evaluations were performed in the same manner. The results are shown in Table 3.

[0133] Comparative Example 3 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 180°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and 0.3 parts of the polyethylene powder (B-1) was replaced with polyethylene powder (B-8) (BET specific surface area: 0.432 m). 2 / g, volume average particle size: 110 μm, bulk density: 0.33 g / cm 3 Except for using 0.3 parts of 1,2-dichloromethane (100% by volume), melting point: 153°C, and ratio of particles having a particle size of 20 μm or more, block copolymer pellets and a pressure-sensitive adhesive sheet were prepared in the same manner as in Example 1, and evaluated in the same manner. The results are shown in Table 3.

[0134] Comparative Example 4 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 240°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and 0.3 parts of the polyethylene powder (B-1) was replaced with polyethylene powder (B-9) (BET specific surface area: 0.330 m 2 / g, volume average particle size: 480 μm, bulk density: 0.39 g / cm 3 Except for using 0.3 parts of 1,2-dichloromethane (100% by volume), melting point: 138°C, and ratio of particles having a particle size of 20 μm or more, the same procedure as in Example 1 was followed to prepare block copolymer pellets and a pressure-sensitive adhesive sheet, which were then evaluated in the same manner. The results are shown in Table 3.

[0135] Comparative Example 5 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 230°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and 0.3 parts of the polyethylene powder (B-1) was replaced with polyethylene powder (B-10) (BET specific surface area: 0.602 m). 2 / g, volume average particle size: 8.5 μm, bulk density: 0.35 g / cm 3 Except for using 0.3 parts of 1.5% by volume of particles having a particle size of 20 μm or more, melting point: 153° C., and a melting point of 153° C., the melting point of 1.5% by volume of particles having a particle size of 20 μm or more, the block copolymer pellets and the pressure-sensitive adhesive sheet were prepared in the same manner as in Example 1, and the evaluations were performed in the same manner. The results are shown in Table

[0136] Comparative Example 6 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 210°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and 0.3 parts of the polyethylene powder (B-1) was replaced with a highly modified hydrocarbon compound powder (B-11) (BET specific surface area: 0.892 m 2 / g, volume average particle size: 8μm, bulk density: 0.24g / cm 3 Except for using 0.3 parts of 1,2-dimethylphenyl ether (1,2-dimethylphenyl ether), melting point: 74°C, and ratio of particles having a particle size of 20 μm or more: 0.5% by volume, block copolymer pellets and a pressure-sensitive adhesive sheet were prepared in the same manner as in Example 1, and evaluations were performed in the same manner. The results are shown in Table 3.

[0137] Comparative Example 7 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 200°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and calcium stearate powder (B-12) (BET specific surface area: 18.44 m) was used in place of 0.3 parts of the polyethylene powder (B-1). 2 / g, volume average particle size: 9.7 μm, bulk density: 0.19 g / cm 3 Except for using 0.3 parts of 1,2-dichloromethane (II), melting point: 148°C, and ratio of particles having a particle size of 20 μm or more: 26.0% by volume, block copolymer pellets and a pressure-sensitive adhesive sheet were prepared in the same manner as in Example 1, and evaluations were performed in the same manner. The results are shown in Table 3.

[0138] Comparative Example 8 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 170°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and 0.3 parts of ethylene bisstearylamide powder (B-13) (volume average particle size: 52 μm, melting point: 161° C.) was used instead of 0.3 parts of the polyethylene powder (B-1), but the same procedure as in Example 1 was used to prepare block copolymer pellets and a pressure-sensitive adhesive sheet, which were then evaluated in the same manner. The results are shown in Table 3.

[0139] Comparative Example 9 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 220°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and talc (B-14) (BET specific surface area: 7.00 m) was used in place of 0.3 parts of the polyethylene powder (B-1). 2 / g, volume average particle size: 8μm, bulk density: 0.25g / cm 3 Except for using 0.3 parts of the particles having a particle size of 20 μm or more (0.5% by volume), block copolymer pellets and a pressure-sensitive adhesive sheet were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 3.

[0140] Comparative Example 10 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 235°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and silica (B-15) (BET specific surface area: 180 m) was used in place of 0.3 parts of the polyethylene powder (B-1). 2 / g, volume average particle size: 10μm, bulk density: 0.10g / cm 3Except for using 0.3 parts of the particles having a particle size of 20 μm or more (0.5% by volume), block copolymer pellets and a pressure-sensitive adhesive sheet were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 3.

[0141] Comparative Example 11 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 240°C. Then, except that 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, block copolymer pellets and an adhesive sheet were prepared and evaluated in the same manner as in Example 2. The results are shown in Table 3.

[0142] Comparative Example 12 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 150°C. Then, except that 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, block copolymer pellets and an adhesive sheet were prepared and evaluated in the same manner as in Example 2. The results are shown in Table 3.

[0143] Example 6 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 215°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and a mixture of 0.24 parts of polyethylene powder (B-1) and 0.06 parts of polypropylene powder (B-5) was used instead of 0.3 parts of polyethylene powder (B-1), and a block copolymer pellet and a pressure-sensitive adhesive sheet were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 4. The ratio of particles having a particle size of 20 μm or more in the mixed powder of polyethylene powder (B-1) and polypropylene powder (B-5) used in Example 6 was 9.0 vol%.

[0144] Example 7 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 220°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and a mixture of 0.27 parts of polypropylene powder (B-2) and 0.03 parts of polypropylene powder (B-5) was used instead of 0.3 parts of polyethylene powder (B-1), but the same procedure as in Example 1 was used to prepare block copolymer pellets and a pressure-sensitive adhesive sheet, which were then evaluated in the same manner. The results are shown in Table 4. The proportion of particles having a particle size of 20 μm or more in the mixed powder of polypropylene powder (B-2) and polypropylene powder (B-5) used in Example 7 was 4.5% by volume.

[0145] Example 8 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 220°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and a mixture of 0.15 parts of polyethylene powder (B-1) and 0.15 parts of polypropylene powder (B-5) was used instead of 0.3 parts of polyethylene powder (B-1), and the block copolymer pellets and adhesive sheet were prepared in the same manner as in Example 1, and evaluated in the same manner. The results are shown in Table 4. The ratio of particles having a particle size of 20 μm or more in the mixed powder of polyethylene powder (B-1) and polypropylene powder (B-5) used in Example 8 was 22.5 vol%.

[0146] Example 9 A pellet molded body of the block copolymer (A-1) obtained in Production Example 1 was obtained in the same manner as in Example 1, except that the molding temperature (resin temperature) in the twin-screw extruder was set to 220°C. Then, 100 parts of the pellet molded body of the block copolymer (A-1) thus obtained was used, and a mixture of 0.15 parts of polypropylene powder (B-2) and 0.15 parts of polypropylene powder (B-5) was used instead of 0.3 parts of polyethylene powder (B-1), and the same procedure as in Example 1 was used to prepare block copolymer pellets and a pressure-sensitive adhesive sheet, which were then evaluated in the same manner. The results are shown in Table 4. The proportion of particles having a particle size of 20 μm or more in the mixed powder of polypropylene powder (B-2) and polypropylene powder (B-5) used in Example 9 was 22.5% by volume.

[0147] Example 10 The block copolymer (A-2) obtained in Production Example 2 was fed into a twin-screw extruder, and the discharged strand was cooled in water at 10°C and then cut into 2.5 mm lengths using a pelletizer to obtain pellets of the block copolymer (A-2) having a diameter of 2.5 mm and a length of 2.5 mm. The molding temperature (resin temperature) of the twin-screw extruder was set to 205°C. Then, except that 100 parts of the pellet molded body of the block copolymer (A-2) thus obtained was used, block copolymer pellets and an adhesive sheet were prepared and evaluated in the same manner as in Example 2. The results are shown in Table 4.

[0148] Example 11 A pellet molded body of the block copolymer (A-2) was obtained in the same manner as in Example 10, except that the block copolymer (A-2) obtained in Production Example 2 was used and the molding temperature (resin temperature) in the twin-screw extruder was set to 210°C. Then, 100 parts of the pellet molded body of the block copolymer (A-2) thus obtained was used, and a mixture of 0.27 parts of polypropylene powder (B-2) and 0.03 parts of polypropylene powder (B-5) was used instead of 0.3 parts of polypropylene powder (B-2), and the block copolymer pellets and adhesive sheet were prepared and evaluated in the same manner as in Example 10. The results are shown in Table 4. The proportion of particles having a particle size of 20 μm or more in the mixed powder of polypropylene powder (B-2) and polypropylene powder (B-5) used in Example 11 was 4.5 vol%.

[0149] Example 12 The block copolymer (A-3) obtained in Production Example 3 was fed into a twin-screw extruder, and the discharged strand was cooled in water at 10°C and then cut into 2.5 mm lengths using a pelletizer to obtain pellets of the block copolymer (A-3) having a diameter of 2.5 mm and a length of 2.5 mm. The molding temperature (resin temperature) of the twin-screw extruder was set to 230°C. Then, except that 100 parts of the pellet molded body of the block copolymer (A-3) thus obtained was used, block copolymer pellets and an adhesive sheet were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 4.

[0150] Example 13 Block copolymer pellets and adhesive sheets were prepared in the same manner as in Example 12, except that a mixture of 0.24 parts of polyethylene powder (B-1) and 0.06 parts of polypropylene powder (B-5) was used instead of 0.3 parts of polyethylene powder (B-1), and were evaluated in the same manner. The results are shown in Table 4. The proportion of particles having a particle size of 20 μm or more in the mixed powder of polyethylene powder (B-1) and polypropylene powder (B-5) used in Example 13 was 9.0 vol %.

[0151] Example 14 The block copolymer (A-4) obtained in Production Example 4 was fed into a twin-screw extruder, and the discharged strand was cooled in water at 10°C and then cut into 2.5 mm lengths using a pelletizer to obtain pellets of the block copolymer (A-4) having a diameter of 2.5 mm and a length of 2.5 mm. The molding temperature (resin temperature) of the twin-screw extruder was set to 215°C. Then, except that 100 parts of the pellet molded body of the block copolymer (A-4) thus obtained was used, block copolymer pellets and an adhesive sheet were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 4.

[0152] Example 15 Block copolymer pellets and adhesive sheets were prepared in the same manner as in Example 14, except that a mixture of 0.18 parts of polyethylene powder (B-1) and 0.02 parts of polypropylene powder (B-5) was used instead of 0.2 parts of polyethylene powder (B-1), and were evaluated in the same manner. The results are shown in Table 4. The proportion of particles having a particle size of 20 μm or more in the mixed powder of polyethylene powder (B-1) and polypropylene powder (B-5) used in Example 15 was 4.5% by volume.

[0153] Example 16 The block copolymer (A-5) obtained in Production Example 5 was fed into a twin-screw extruder, and the discharged strand was cooled in water at 10°C and then cut into 2.5 mm lengths using a pelletizer to obtain pellets of the block copolymer (A-5) having a diameter of 2.5 mm and a length of 2.5 mm. The molding temperature (resin temperature) of the twin-screw extruder was set to 225°C. Then, except that 100 parts of the pellet molded body of the block copolymer (A-5) thus obtained was used, block copolymer pellets and an adhesive sheet were prepared and evaluated in the same manner as in Example 2. The results are shown in Table 4.

[0154] Example 17 Block copolymer pellets and adhesive sheets were prepared in the same manner as in Example 16, except that a mixture of 0.16 parts of polypropylene powder (B-2) and 0.04 parts of polypropylene powder (B-5) was used instead of 0.2 parts of polypropylene powder (B-2), and were evaluated in the same manner. The results are shown in Table 4. The proportion of particles having a particle size of 20 μm or more in the mixed powder of polypropylene powder (B-2) and polypropylene powder (B-5) used in Example 17 was 4.5 vol%.

[0155] Comparative Example 13 The block copolymer (A-2) obtained in Production Example 2 was fed into a twin-screw extruder, and the discharged strand was cooled in water at 10°C and then cut into 2.5 mm lengths using a pelletizer to obtain pellets of the block copolymer (A-2) having a diameter of 2.5 mm and a length of 2.5 mm. The molding temperature (resin temperature) of the twin-screw extruder was set to 210°C. Then, except for using 100 parts of the pellet molded body of the block copolymer (A-2) thus obtained, block copolymer pellets and an adhesive sheet were prepared and evaluated in the same manner as in Comparative Example 1. The results are shown in Table 4.

[0156] Comparative Example 14 The block copolymer (A-3) obtained in Production Example 3 was fed into a twin-screw extruder, and the discharged strand was cooled in water at 10°C and then cut into 2.5 mm lengths using a pelletizer to obtain pellets of the block copolymer (A-3) having a diameter of 2.5 mm and a length of 2.5 mm. The molding temperature (resin temperature) of the twin-screw extruder was set to 230°C. Then, using 100 parts of the pellet molded body of the block copolymer (A-3) thus obtained, and changing the amount of the polyethylene powder (B-7) used from 0.3 parts to 0.2 parts, block copolymer pellets and a pressure-sensitive adhesive sheet were prepared and evaluated in the same manner as in Comparative Example 2. The results are shown in Table 4.

[0157] Comparative Example 15 The block copolymer (A-4) obtained in Production Example 4 was fed into a twin-screw extruder, and the discharged strand was cooled in water at 10°C and then cut into 2.5 mm lengths using a pelletizer to obtain pellets of the block copolymer (A-4) having a diameter of 2.5 mm and a length of 2.5 mm. The molding temperature (resin temperature) of the twin-screw extruder was set to 215°C. Then, using 100 parts of the pellet molded body of the block copolymer (A-4) thus obtained, and changing the amount of the polyethylene powder (B-9) used from 0.3 parts to 0.2 parts, block copolymer pellets and a pressure-sensitive adhesive sheet were prepared in the same manner as in Comparative Example 4, and were evaluated in the same manner. The results are shown in Table 4.

[0158] Comparative Example 16 The block copolymer (A-5) obtained in Production Example 5 was fed into a twin-screw extruder, and the discharged strand was cooled in water at 10°C and then cut into 2.5 mm lengths using a pelletizer to obtain pellets of the block copolymer (A-5) having a diameter of 2.5 mm and a length of 2.5 mm. The molding temperature (resin temperature) of the twin-screw extruder was set to 235°C. Then, using 100 parts of the pellet molded body of the block copolymer (A-5) thus obtained, and changing the amount of polyethylene powder (B-10) used from 0.3 parts to 0.2 parts, block copolymer pellets and a pressure-sensitive adhesive sheet were prepared in the same manner as in Comparative Example 5, and evaluated in the same manner. The results are shown in Table 4.

[0159] Example 18 When pellets were obtained using the block copolymer (A-1) obtained in Production Example 1, the molding temperature (resin temperature) in the twin-screw extruder was set to 170°C, and 0.5 parts of polystyrene was further blended with 100 parts of the block copolymer (A-1) and pelletized to obtain pellets of the block copolymer (A-1) blended with polystyrene. Note that a homopolymer of styrene was used as the polystyrene (the same applies to the following Examples 19 to 23). Then, except that 100 parts of pellet molded body of block copolymer (A-1) blended with 0.5 parts of polystyrene was used, block copolymer pellets and adhesive sheets were prepared in the same manner as in Example 2, and were evaluated in the same manner. The results are shown in Table 5.

[0160] Example 19 When pellets were obtained using the block copolymer (A-1) obtained in Production Example 1, the molding temperature (resin temperature) in the twin-screw extruder was set to 200°C, and 3.5 parts of polystyrene were further blended with 100 parts of the block copolymer (A-1) and pelletized to obtain a pellet-molded product of the block copolymer (A-1) blended with polystyrene. Then, except that 100 parts of pellet molded body of block copolymer (A-1) blended with 3.5 parts of polystyrene was used, block copolymer pellets and adhesive sheets were prepared in the same manner as in Example 2, and were evaluated in the same manner. The results are shown in Table 5.

[0161] Example 20 When pellets were obtained using the block copolymer (A-4) obtained in Production Example 4, the molding temperature (resin temperature) in the twin-screw extruder was set to 210°C, and 0.8 parts of polystyrene was further blended with 100 parts of the block copolymer (A-4) and pelletized to obtain a pellet-molded product of the block copolymer (A-4) blended with polystyrene. Then, 100 parts of pellets of block copolymer (A-4) containing 0.8 parts of polystyrene were used, and the amount of polypropylene powder (B-2) was changed from 0.3 parts to 0.2 parts, but the block copolymer pellets and adhesive sheet were prepared in the same manner as in Example 2, and evaluated in the same manner. The results are shown in Table 5.

[0162] Example 21 When pellets were obtained using the block copolymer (A-4) obtained in Production Example 4, the molding temperature (resin temperature) in the twin-screw extruder was set to 225°C, and 4.1 parts of polystyrene were further blended with 100 parts of the block copolymer (A-4) and pelletized to obtain a pellet-molded product of the block copolymer (A-4) blended with polystyrene. Then, 100 parts of pellet molded body of block copolymer (A-4) containing 4.1 parts of polystyrene was used, and the amount of polypropylene powder (B-2) was changed from 0.3 parts to 0.2 parts, and the block copolymer pellets and adhesive sheet were prepared in the same manner as in Example 2, and evaluated in the same manner. The results are shown in Table 5.

[0163] Example 22 When pellets were obtained using the block copolymer (A-1) obtained in Production Example 1, the molding temperature (resin temperature) in the twin-screw extruder was set to 205°C, and 3.5 parts of polystyrene were further blended with 100 parts of the block copolymer (A-1) and pelletized to obtain pellets of the block copolymer (A-1) blended with polystyrene. Then, 100 parts of pellets of block copolymer (A-1) containing 3.5 parts of polystyrene were used, and a mixture of 0.24 parts of polyethylene powder (B-1) and 0.06 parts of polypropylene powder (B-5) was used instead of 0.3 parts of polypropylene powder (B-2). Except for this, block copolymer pellets and a pressure-sensitive adhesive sheet were prepared in the same manner as in Example 19, and were evaluated in the same manner. The results are shown in Table 4. The ratio of particles having a particle size of 20 μm or more in the mixed powder of polyethylene powder (B-1) and polypropylene powder (B-5) used in Example 22 was 9.0% by volume.

[0164] Example 23 When pellets were obtained using the block copolymer (A-4) obtained in Production Example 4, the molding temperature (resin temperature) in the twin-screw extruder was set to 230°C, and 4.1 parts of polystyrene were further blended with 100 parts of the block copolymer (A-4) and pelletized to obtain a pellet-molded product of the block copolymer (A-4) blended with polystyrene. Then, 100 parts of pellets of block copolymer (A-4) containing 4.1 parts of polystyrene were used, and 0.16 parts of polypropylene powder (B-2) and 0.04 parts of polypropylene powder (B-5) were used instead of 0.2 parts of polypropylene powder (B-2). Except for this, block copolymer pellets and adhesive sheets were prepared in the same manner as in Example 21, and were evaluated in the same manner. The results are shown in Table 4. The proportion of particles having a particle size of 20 μm or more in the mixed powder of polypropylene powder (B-2) and polypropylene powder (B-5) used in Example 23 was 9.0% by volume.

[0165] [Table 3]

[0166] [Table 4]

[0167] [Table 5]

[0168] As shown in Tables 3 to 5, the BET specific surface area of ​​100 parts of the pellet molded body of the block copolymer (A) is 0.50 to 3.00 m 2 / g, volume average particle size is 2.0 to 20 μm, bulk density is 0.10 to 0.34 g / cm 3 and 0.01 to 5 parts of a hydrocarbon dusting agent (B) having a melting point of 75°C or higher, and a Shore A hardness of 10 to 80 and a BET specific surface area of ​​0.001 to 0.05 m. 2 The block copolymer pellets having a molecular weight of 1000 to 1500 g / g were suppressed in terms of dust generation, had excellent blocking resistance and transparency, and exhibited high adhesion to the adherend (Examples 1 to 23).

[0169] In particular, when a hydrocarbon-based dusting agent (B) containing particles having a particle size of 20 μm or more at a ratio of 3 to 40 volume % was used, the results showed that the blocking resistance was particularly excellent (Examples 6 to 9, 11, 13, 15, 17, 22, and 23). Furthermore, when the pellet molded body further contained 0.5 to 5.0 parts of a polystyrene polymer per 100 parts of the block copolymer (A), the blocking resistance was also particularly excellent (Examples 18 to 23).

[0170] On the other hand, when a dusting agent that was not made of a hydrocarbon compound was used, or when any of the BET specific surface area, volume average particle size, bulk density, and melting point was outside the range specified in the present invention, dusting occurred, the blocking resistance and transparency were poor, or the adhesion to the substrate was low (Comparative Examples 1 to 10, 13 to 16). In addition, the BET specific surface area of ​​the block copolymer pellet itself is 0.001 m 2 / g and 0.05m 2In all cases where the thickness was more than 1 / g, the blocking resistance was poor (Comparative Examples 11 and 12).

Claims

1. A block copolymer pellet comprising 100 parts by weight of a pellet-formed body of a block copolymer (A) and 0.01 to 5 parts by weight of a hydrocarbon dusting agent (B), The block copolymer (A) has at least one aromatic vinyl polymer block and at least one conjugated diene polymer block, The hydrocarbon dusting agent (B) has a BET specific surface area of ​​0.50 to 3.00 m 2 / g, volume average particle size is 2.0 to 20 μm, and bulk density is 0.10 to 0.34 g / cm 3 , the melting point is 75°C or higher; The block copolymer pellets have a Shore A hardness of 10 to 80 and a BET specific surface area of ​​0.001 to 0.05 m as measured by a Kr adsorption method. 2 / g of block copolymer pellets.

2. 2. The block copolymer pellet according to claim 1, wherein the hydrocarbon dusting agent (B) contains particles having a particle diameter of 20 μm or more in a ratio of 3 to 40 volume %.

3. 3. The block copolymer pellet according to claim 1, wherein the pellet-shaped product further contains 0.5 to 5.0 parts by weight of a polystyrene polymer based on 100 parts by weight of the block copolymer (A).

4. 4. The block copolymer pellet according to claim 1, wherein the hydrocarbon-based dusting agent (B) is a dusting agent made of a polyolefin-based polymer.

5. 5. The block copolymer pellet according to claim 1, wherein the content of aromatic vinyl monomer units in the block copolymer (A) is 10 to 50% by weight.

6. The block copolymer pellet according to any one of claims 1 to 5, wherein the aromatic vinyl polymer block is a polymer block containing 80% by weight or more of styrene units, and the conjugated diene polymer block is a polymer block containing 80% by weight or more of isoprene units.

7. A pressure-sensitive adhesive composition obtained by using the block copolymer pellets according to any one of claims 1 to 6.

8. A stretch film obtained by using the block copolymer pellets according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Thermoplastic elastomer pellet and molded article

    JP2002371136A

  • Thermoplastic resin laminated cloth molded article and waterproof article

    JP2003136643A

  • Triblock copolymer pellet and polymer composition

    JP2007308525A

  • Block copolymer composition and film

    JP2016069565A

  • Free flowing powder composition, process for its preparation and homogeneous layer derived therefrom

    US6013717A